Problems of market innovation development in within ukrainian economy`s institutionalization - Сидоров, Вадим; Шедякова, Татьяна (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
The article studies questions of  innovative activity in the modern economy of Ukraine. The article describes the general provisions in the field of innovation and innovation development; the authors’ approaches to the definition of innovation as an economic category and improved theoretical and methodological  aspects of innovations intensification also. New methods of successful formation of innovative processe control system are offered.